Risk Regulation in the Single Market The Governance of Pharmaceuticals and Foodstuffs in the European Union - Krapohl, Sebastian. (Palgrave Studies in European Union Politics,, 2008)
This book demonstrates how the Thalidomide catastrophe of the 1960s and the BSE crisis of the 1990s led to regulatory regimes for pharmaceuticals and foodstuffs in Europe. However, the developmental paths of these regimes differ – and so does the efficiency and legitimacy of regulatory policy-making.